THE DEVELOPMENT OF INTERACTIVE MULTIMEDIA WITH DRILL AND PRACTICE MODEL ON MULTIMEDIA II (TWO DIMENTION ANIMATION) COURSE IN POLITEKNIK GANESHA GURU - Pujawan, Kadek Agus Hendra (LPPM Undiksha, 2018)
This study aims (1) To create interactive multimedia design with drill and practice model at Multimedia II (animation 2 dimension) course, (2) To know the feasibility of interactive multimedia with drill and practice model at Multimedia II (animation 2 dimension) course.Â The type of study used was Research and Development by using development model of Dick & Carey. This study involved the first grade students of Informatika Management program at Politeknik Ganesha Guru. Based on the result of data analysis which is derived from the content feasibility aspect performed by the content expert showed that the product was acceptable with SAP of Multimedia II (animation 2 dimension) course.Â In the tests which were performed by the media expert obtained 85% calculation results are in good qualification.Â In the tests which were done by the design of the learning expert obtained 88% calculation results are in good qualification. The user/lectures gave good response. Field trials that were conducted obtained a calculation of 89% are in good qualification.